2019
DOI: 10.1097/hs9.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Thrombocytosis after Induction Chemotherapy is a Strong Biomarker for Favorable Outcome in AML Patients

Abstract: Whereas the molecular events underlying acute myeloid leukemia (AML) are increasingly identified, dynamics of hematologic recovery following induction chemotherapy remain mysterious. Platelet recovery may vary between incomplete and excess recovery among patients achieving remission. We analyzed platelet recovery after the first induction cycle in 291 consecutive AML patients. We defined excess platelet rebound (EPR) as platelet increase above 500 G/L. We observed EPR in 120 (41.2%) patients. EPR+ patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Currently, the selection of appropriate therapeutic methods for AML mainly depends on the age of the patient and risk stratification, including cytogenetic and molecular features [ 4 ]. Nevertheless, the data collected after the initiation of AML treatment can potentially be as useful as the pretreatment characteristics [ 5 ]. Therefore, post-treatment data may be used in developing treatment decision-making strategies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the selection of appropriate therapeutic methods for AML mainly depends on the age of the patient and risk stratification, including cytogenetic and molecular features [ 4 ]. Nevertheless, the data collected after the initiation of AML treatment can potentially be as useful as the pretreatment characteristics [ 5 ]. Therefore, post-treatment data may be used in developing treatment decision-making strategies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rebound thrombocytosis has been described in patients with AML treated with intensive induction chemotherapy and is correlated with favorable outcomes. 1 Larger studies will be needed to determine if rebound thrombocytosis is also correlated with durability of response and survival.…”
mentioning
confidence: 99%
“…Hyperuricemia and abnormal ambulatory blood pressure monitoring (ABPM) represent two established modifiable risk factors associated with development of CKD. We performed a cross-sectional study of this cohort at baseline and identified that hyperuricemia and abnormal ABPM were associated with lower eGFR at baseline 1. This prospective study evaluated the annual change in estimated GFR (eGFR) among patients with and without hyperuricemia, nocturnal hypertension, and abnormal nocturnal dipping.…”
mentioning
confidence: 99%
“…Rebound thrombocytosis after induction chemotherapy occurs in up to 40% of patients with acute myeloid leukemia (AML) and may be associated with a favourable outcome [1] . Despite being a recognised cause of secondary thrombocytosis, this rebound phenomenon remains a trigger for the investigation of the myeloproliferative neoplasm (MPN)-associated, driver mutations of JAK2 V617F, CALR exon 9 and MPL exon 10 to determine whether the AML had transformed from an underlying MPN in whom the clinical management remains challenging [2] .…”
mentioning
confidence: 99%